Scalar Containment of Energy Justice and Its Democratic Discontents: Solar Power and Energy Poverty Alleviation - Nordholm, Amber; Sareen, Siddharth (Frontiers in Sustainable Cities, 2021)
The threats climate change poses require rapid and wide decarbonization efforts in the energy sector. Historically, large-scale energy operations, often instrumental for a scaled and effective approach to meet decarbonization goals, undergird energy-related injustices. Energy poverty is a multi-dimensional form of injustice, with relevance to low-carbon energy transitions. Defined as the condition of being unable to access an adequate level of household energy services, energy poverty persists despite the emergence of affordable renewable energy technologies, such as solar photovoltaics (PV). Historical injustices and the modularity of solar PV combine to offer new possibilities in ownership, production and distribution of cost-competitive, clean and collectively scalable energy. Consequently, emerging policy priorities for positive energy districts call into question the traditional large-scale modality of energy operations. We report from a case study of solar power in Lisbon, a frontrunner in urban energy transitions while also home to high energy poverty incidence. The study focuses on scalar aspects of justice in energy transitions to investigate whether and how solar PV can alleviate urban energy poverty. It features 2 months of fieldwork centered on community and expert perspectives, including semi-structured interviews and field observations. We mobilize a spatial energy justice framework to identify justice aspects of multi-scalar solar PV uptake. By showing how energy justice is shaped in diverse ways at different scales, we demonstrate ways in which scale matters for just urban energy transitions. We argue that small- and medium-scaled approaches to electricity distribution, an integral component of positive energy districts, can address specific justice concerns. However, even as such approaches gain attention and legitimacy, they risk structurally excluding socio-economically vulnerable users, and proceed slowly relative to large-scale solar rollout.